Effects of Water and Nitrogen Addition on the Seed Yield and Germination Characteristics of the Perennial Grass Leymus chinensis (Trin.) Tzvel - Zhao, Dan-Dan; Ma, Hong-Yuan; Wang, Lei; Li, Shao-Yang; Qi, Wen-Wen; Ma, Meng-Yao; Xia, Jiang-Bao (Frontiers in Environmental Science, 2021)
The reproductive characteristics of plants are likely affected by climate change e.g., changes in precipitation patterns and nitrogen deposition, but few studies have examined the effects of these ecological agents of selection on the seed yield and germination characteristics of perennial grasses. Here, we conducted a multiple-year pot experiment with Leymus chinensis, a common perennial grass in the eastern region of the Eurasian steppe zone, which was grown under three water treatments with and without nitrogen addition. The seed yield of L. chinensis increased with precipitation and was highest (7.0 g/pot) under 747 mm of precipitation with nitrogen addition (10.5 g/m2). Seed yield was positively correlated with heading number, tiller number, and grain number per spike, and the heading number was a critical factor affecting seed yield. Seed germination percentage and the time to obtain 50% germination were affected by environmental cues experienced by the mother plants.